(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
The study investigates how the formations of the self-identity of the human entity, while trying to understand the world and the self, and the patterns of experiencing freedom, created by the potential of powers of performance that originates from the search for self-identity and also shapes the freedom and responsibilities of pedagogical relationships, are represented in the ethos of getting at truth and justice, present in every human being. In case we succeed in finding good enough solutions that enable the free movement between the individual and institutional values and interest, we can get closer to grasp the habitualised concept of the pedagogical culture of the ethos. The conclusion of the study suggests that good enough practice of education which is able to react sensitively to the changes of socialisation may support the self-development attempts of students to fill the gaps of their self-identity, re-create their self and find the possible means of understanding.